The impact of green organizational identity on green innovation at Jordanian food and beverage companies - Hasan Al-Zu’bi; Ahmad Albloush (Problems and Perspectives in Management, 2022)
Integrating environmental objectives into an organization’s mission and strategies improves the organization’s image as a socially responsible organization and helps it take a leading position of advantage. Due to the increasing pressures towards sustainability and environmental policies, organizations are making efforts in this direction. This study is aimed at identifying the impact of green organizational identity (GOI) on green innovation (GI). Data were collected from 168 employees working in food and beverage industry companies listed on the Amman Stock Exchange. SPSS was employed to analyze the data and test the hypothesis. The study finds a significant positive effect of GOI on GI product and GI process. The study recommends that companies show interest in GOI for their role in raising GI levels. Due to cultural differences between countries that limit the generalizability of the study results, it is recommended to conduct another study in Western culture to determine their applicability.